DEVELOPMENT AND VALIDATION OF AUGMENTED REALITY-BASED POETRY LEARNING MEDIA FOR ENHANCING LITERARY ANALYSIS SKILLS AMONG SENIOR HIGH SCHOOL STUDENTS - Romince Simatupang; Baharuddin; Dina Ampera; Abdurahman Adisaputera; R. Mursid; Amirhud Dalimunthe (RADJA PUBLIKA, 2026)
This study aimed to develop, validate, and evaluate the effectiveness of Augmented Reality (AR)-based poetry learning media in enhancing students’ literary analysis skills in Indonesian language learning. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation phases. The participants were Grade X students of SMA Negeri 1 Paranginan, Indonesia, during the 2025/2026 academic year. The developed AR media was designed to visualize abstract poetic elements, including imagery, symbolism, tone, theme, and message, through interactive three-dimensional objects and multimedia features. Data were collected through expert validation sheets, student response questionnaires, observations, and literary analysis achievement tests. The validation results indicated that the AR media was highly feasible for instructional use, with material expert validation reaching 80.6%, instructional design expert validation 92.0%, and media expert validation 88.3%. Practicality testing demonstrated positive student responses, with average scores exceeding 85% across individual, small-group, and field trials. The effectiveness analysis revealed that students who learned using the AR media achieved significantly higher literary analysis skills than those receiving conventional instruction. The experimental group obtained a mean score of 83.11, while the control group achieved 76.08. Independent-samples t-test results showed a statistically significant difference between groups (p < .05). These findings suggest that AR-based poetry learning media effectively enhances students’ engagement, comprehension, and literary analysis skills by transforming abstract poetic concepts into meaningful and interactive learning experiences. Therefore, the developed media is considered valid, practical, and effective for senior high school poetry instruction.